Model Management Of MSME Production Of Seaweed Farmers In Sampulungan Village, Kab. Takalar Provinsi Of South Sulawesi Indonesia - St. Hatidja -; Junaidin -; Muh Rizal Halim; Lina Mariana; Syarifuddin - (Journal of Entrepreneur, Business and Management, 2023)
Seaweed is one of the businesses carried out by the majority of the population in the village of Sampulungan. One type of business innovation from seaweed is seaweed dodol, seaweed syrup, gelatin seaweed, and seaweed candy. The seaweed business carried out by seaweed farmers is one of the mainstay businesses of the residents of Sampulungan Village which is expected to be able to increase economic value. The seaweed business is carried out simply and based on hereditary experience from its predecessors so that the added value of the business has not been able to contribute optimal economic value for the seaweed business sector and public welfare. Concrete efforts are needed for simple patterns to become business with appropriate managerial patterns under the real conditions in the community. This research was conducted in the village of Sampulungan, Takalar Regency to formulate the MSME production management model of seaweed farmer groups. This type of research uses qualitative and quantitative data with qualitative descriptive analysis methods. The results of the research formulate a model of production management and raw materials are seaweed management consisting of raw material inventory, production process, total production capacity per harvest, number of workers.